Efficacy and Safety of Bisphosphonates for Low Bone Mineral Density After Kidney Transplantation: A Meta-Analysis. Issue 5 (February 2016) - Kan, Shun-Li; Ning, Guang-Zhi; Chen, Ling-Xiao; Zhou, Yong; Sun, Jing-Cheng; Feng, Shi-Qing
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: In patients with low bone mineral density (BMD) after kidney transplantation, the role of bisphosphonates remains unclear. We performed a systematic review and meta-analysis to investigate the efficacy and safety of bisphosphonates. We retrieved trials from PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception through May 2015. Only randomized controlled trials that compared bisphosphonate-treated and control groups of patients with low bone mineral density after kidney transplantation were included. The primary outcomes were the percent change in BMD, the absolute change in BMD, and the BMD at the end of study at the lumbar spine. The results were expressed as the mean difference (MD) or relative risk (RR) with the 95% confidence interval (CI). We used a random-effects model to pool the outcomes. We included 17 randomized controlled trials with 1067 patients. Only 1 included trial was found to be at low risk of bias. The rest of the included studies were found to have high to uncertain risk of bias. Compared with the control group, those who received bisphosphonates had a significant increase in percent change in BMD (mean difference [MD] = 5.51, 95% confidence interval [CI] 3.22–7.79, P < 0.00001) and absolute change in BMD (MD = 0.05, 95% CI 0.04–0.05, P < 0.00001), but a nonsignificant increase in BMD at the end of the study (MD = 0.02, 95% CI −0.01 to 0.05, P = 0.25) at the lumbar spine. Bisphosphonates resulted in a significant improvement in percent change in BMD (MD = 4.95, 95% CI 2.57–7.33, P < 0.0001), but a nonsignificant improvement in absolute change in BMD (MD = 0.03, 95% CI −0.00 to 0.06, P = 0.07) and BMD at the end of the study (MD = −0.01, 95% CI −0.04 to 0.02, P = 0.40) at the femoral neck. No significant differences were found in vertebral fractures, nonvertebral fractures, adverse events, and gastrointestinal adverse events. Bisphosphonates appear to have a beneficial effect on BMD at the lumbar spine and do not significantly decrease fracture events in recipients. However, the results should be interpreted cautiously due to the lack of robustness and the heterogeneity among studies.